Prevalence and prognostic significance of silent myocardial ischemia in patients after myocardial infarction - Deljanin-Ilić Marina Ž.; Ilić Stevan N. (Vojnosanitetski Pregled)
Background/Aim. Silent myocardial ischemia (MI) can be detected in subjects with any symptoms, in patients after myocardial infarction and in coronary patients who have episodes of symptomatic, as well as of silent MI. This study was carried out to evaluate the frequency, characteristics and prognostic significance of silent MI detected in stress echocardiography test in patients after myocardial infarction. Methods. In 210 patients within three months after myocardial infarction exercise test was performed. In those patients with ischemic ST depression on exercise electrocardiogram, in order to confirm MI stress echocardiography was additionally performed. To assess the incidence of major cariovascular events, all the patients were followed at least five years after the first myocardial infraction. Results. Out of 210 patients 88 (42%) had ischemic response during stress echocardiography test. Out of 88 patients with MI 54 (61%) had anginal pain (patients with symptomatic MI), while 34 (39%) were free of symptoms (patients with silent MI). Level of exercise test, heart rate, time to the onset of ST segment depression, and the magnitude of ST segment depression were similar in both subgroups of the patients with MI. Duration of exercise test was longer in patients with silent MI (p < 0.05). Wall motion score index during stress echocardiography was higher in patients with symptomatic MI (p < 0.05). Coronary angiography findings were similar in patients with silent and those with symptomatic MI. During a five- yearsfollow- up period the occurrence of major cardic events (cardiac mortality and recurrent myocardial infarction) was similar in both subgroups of the patients with MI. Conclusion. In more than one third of patients after myocardial infarction silent MI during stress echocardiography was detected. The patients with silent ischemia had longer duration of exercise test and smaller wall motion score index on stress echocardiography. There was no difference in coronary angiography finding between patients with silent and those with symptomatic MI. The incidence of major cardiac events during a five- years- follow-up was similar in the patients with silent and those with symptomatic MI. .